Hubungan Penyakit Penyerta dengan Derajat Keparahan Pasien Covid-19 di RSUD Kabupaten Buleleng - Kade Adiatmika, Ida Ayu; Denny Yuliyatni, Putu Cintya (Universitas Pahlawan Tuanku Tambusai, 2025)
The degree of severity of COVID-19 patients is influenced by several factors, one of which is comorbidities. The degrees of severity in COVID-19 patients can result in death. In Buleleng Regency, 90% of COVID-19 patient deaths are experienced by patients with co-morbidities. This study aims to determine the relationship between comorbidities and the degree of severity in COVID-19 patients at Buleleng District Hospital. This study uses a type of quantitative analytic cross-sectional study. The sample size was calculated using the two-sided test formula and was selected by simple random sampling. Secondary data was taken from 170 medical records of COVID-19 patients who started treatment in July 2021 and finished receiving treatment in December 2021. The variables studied included individual characteristics, clinical characteristics, and the degree of patient severity. Data were analyzed by logistic regression test. The results showed that the majority (70.5%) of COVID-19 patients experienced moderate severity. Factors related to the severity of COVID-19 patients include age (aOR = 4.8; 95% CI: 1.4-15.6) and history of comorbidities (aOR = 11.4; 95% CI: 4 ,9-26,6). Initial assessment of severity may allow prioritization of treatment and supportive measures in COVID-19 patients. Health promotion is needed for the community to reduce the risk of severity that may occur, especially for people with comorbidities.